Genetic diversity of Jujube (Ziziphus jujuba Mill.) germplasm based on vegetative and fruits physicochemical characteristics from Golestan province of Iran - Ghazaeian, Mina (Comunicata Scientiae, 2015)
Jujube fruits have sweet flavor and are rich of A, C and B vitamins and mineral nutrients. It used as table fruit, nut fruit, medicinal and ornamental plant. In this study 10 different ecotypes of Ziziphus jujuba Mill. were collected from different regions of Golestan province of Iran and their vegetative (stem annual growth, thorn length, leaf length, leaf width and petiole length) and fruit physicochemical characteristics (fruit length, fruit width, fruit weight, humidity percent, flesh/stone ratio, stone weight, stone length, stone width, vitamin C content, pH and total soluble solid (TSS)) were evaluated between years 2009-2011. The results of this study showed significantly differences between ecotypes from different regions. Different evaluated traits of Lemesk ecotype were significantly different from the other ecotypes; this result was corroborated by cluster analysis. The ecotypes were separated according to their geographic origin. So it can be concluded that the climate effects is very important for existence of qualitative and quantitative characteristics of jujube.